Association between Sleep-Disordered Breathing during Pregnancy and Maternal and Fetal Outcomes: An Updated Systematic Review and Meta-Analysis - Li, Liwen; Zhao, Kena; Hua, Jin; Li, Shenghui (Frontiers in Neurology, 2018)
Background: Due to the high prevalence in pregnant women and potential association with pregnancy complications or perinatal outcomes, sleep-disordered breathing (SDB) has become an increasing concern. Methods: Pubmed and Embase were retrieved from inception until 2017 to conduct a meta-analysis to explore the association of SDB and several outcomes during gestation. A stratified analysis differentiated by the type of SDB (snoring alone/OSA) was also performed. Pooled odds ratios were produced for binary outcomes. Weighted mean differences were also produced for continuous outcomes. Sensitivity analysis was performed to identify the impact of individual studies on summary results and estimation of publication bias was performed by funnel plot. Results: 35 studies with a total of 56,751,837 subjects were included. SDB during pregnancy was associated with a significantly increased risk of gestational diabetes mellitus (GDM), pregnancy-induced hypertension (PIH), and preeclampsia (PEC), but not significantly associated with fetal maternal outcomes, namely APGAR score and birth weight. Moreover, OSA was linked with an increasing risk of GDM, PIH, PEC and preterm birth (PTB) while snoring appeared to increase the risk of GDM, PIH and PEC. Conclusions: The finding provided potential evidence for association between SDB and adverse perinatal outcomes. SDB increased the risk of some pregnancy complications while its influence to fetal outcomes was not clear.